Strategi pengembangan layanan perpustakaan dalam menggunakan media sosial di perguruan tinggi - Suherman Suherman (UIN Sumatera Utara, 2018)
This article discusses information technology development strategies for higher education library services. college libraries have specific strategies in developing information technology-based library services more in facing the current industrial revolution 4.0 era in order to improve the quality of services in order to support their educational institutions in realizing